Controversial Issue Learning Model: Social Studies Learning Outcomes at Elementary School - Dean R. Matital; Elsinora Mahananingtyas; Leonid Ritiauw (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Innovative learning strategies are needed to help elementary school students understand complicated social studies topics like ethnic and religious diversity. This report is based on Nuruwe Christian Elementary School fourth graders' dismal learning outcomes. This study examines whether the controversial issue learning paradigm improves social studies learning in Nuruwe Christian Elementary School fourth graders. Two cycles of Classroom Action Research (CAR) were used. Each cycle includes planning, action, observation, and reflection. The study included 12 Nuruwe Christian Elementary School fourth graders. Testing, observation, and documentation using test and observation sheets acquired data. Data analysis was carried out using individual assessment techniques and calculating the average value of learning outcomes. The results of the study indicate that the application of the controversial issue learning model to the material about ethnic and religious diversity in my country can significantly improve student learning outcomes. This model has been proven to help teachers in presenting more dynamic and effective learning variations in the classroom. This study provides innovative learning strategies that assist teachers in creating meaningful and beneficial learning activities. In addition, this study enriches references regarding the use of controversial issues as educational media to increase student engagement and academic achievement at the elementary school level.